2021
DOI: 10.3390/polym13142312
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Propolis Ointment with the Addition of 1% Nanosilver in the Treatment of Experimentally-Evoked Burn Wounds

Abstract: The main objective of this study was to assess the pharmacological efficacy of ointments containing 1% propolis and 1% nanosilver, compared to the conventional treatment of burn wounds. In the evaluation of the results, we used clinical observation of scars, microbiological examinations, pathomorphological examinations, and analysis of free radicals. The analysis of the experiment results concerning the therapeutic effectiveness of the propolis ointment revealed its wide-ranging antibacterial action (against G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The findings on propolis' actions regarding neovascularization and angiogenesis have shown contradicting results. In some studies, propolis positively affects angiogenesis (Abdel-Wahed et al, 2013;Nindra et al, 2021;Staniczek et al, 2021;Sungkar et al, 2021), and in other studies it negatively affects angiogenesis (Chikaraishi et al, 2010;Lima et al, 2014;Melo et al, 2018). Sungkar et al (2021) reported that EEP from Mount Lawu, Indonesia has angiogenic effects or promotes angiogenesis through decreased malondialdehyde blood levels and IL-6 blood levels, and an increase in vascular endothelial growth factor (VEGF) blood levels.…”
Section: Stimulation Of Angiogenesis and Neovascularizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings on propolis' actions regarding neovascularization and angiogenesis have shown contradicting results. In some studies, propolis positively affects angiogenesis (Abdel-Wahed et al, 2013;Nindra et al, 2021;Staniczek et al, 2021;Sungkar et al, 2021), and in other studies it negatively affects angiogenesis (Chikaraishi et al, 2010;Lima et al, 2014;Melo et al, 2018). Sungkar et al (2021) reported that EEP from Mount Lawu, Indonesia has angiogenic effects or promotes angiogenesis through decreased malondialdehyde blood levels and IL-6 blood levels, and an increase in vascular endothelial growth factor (VEGF) blood levels.…”
Section: Stimulation Of Angiogenesis and Neovascularizationmentioning
confidence: 99%
“…T A B L E 1 List of research using propolis for wound care in different forms of topical delivery systems. Moon et al, 2018;Staniczek et al, 2021;Stojko et al, 2020).…”
Section: Dosage Considerations and Safety Profile Of Propolis-based P...mentioning
confidence: 99%
See 2 more Smart Citations
“…The main ingredients of propolis are aromatic acids (for example, cinnamic acid, caffeic acid, ferulic acid), aromatic esters (cinnamic and caffeic acid ether esters), volatile compounds (geraniol, nerol, farnesol, β-eudesmol), aromatic compounds (vanillin), hydrocarbons (eicosan, tri-cosan, pentacosan), steroids (cholinesterol, fucosterol, stigmas-terol), enzymes (αamylase, β-amylase), flavonoids (tecto-chrysin, pinobanksin, pinocembrin, chrysin, galangin, apigenin, kaempferol), acids (palmitic acid, melissic acid, cerotic acids), micro and macro nutrients (Ca, K, Mg, Na, Zn, Fe, Mn, Al, Ba, Cl), vitamins (B1, B2, B6, C, E) and volatile oil compounds (Kubiliene et al, 2014). In recent years, studies and research on propolis have increased considerably in terms of internal food supplement and external medical purposes (Namratha et al, 2013;Afkhamizadeh et al, 2018;Rojczyk et al, 2020;Staniczek et al 2021;Furukawa et al 2021;da Rosa et al 2022). There are also some propolis combined with beewax and some other herbal substances such as almond oil, olive oil, sunflower oil, etc.…”
Section: Introductionmentioning
confidence: 99%